(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To understand the characteristics of elderly patients with aortic disease treated at the Vietnam National Heart Institute in order to determine the incidence of aortic aneurysms and dissections, and to gather necessary information for more optimal treatment. Subjects and methods: This is a descriptive, retrospective study of 161 patients over 60 years old, treated at the Vietnam National Heart Institute from August 2024 to August 2025. Results: The results from the survey showed that the main reason for hospitalization was chest pain and abdominal pain. The ratio of males to females is higher (77% vs. 23%), with a hypertension rate of 90%. The conditions of abdominal aortic aneurysm, thoracic aortic aneurysm, and thoracic aortic dissection accounted for 50.9%, 17.4%, and 31.7%, respectively. The rates of surgical, endovascular, and medical treatment were 5.6%, 34.8%, and 59.6%, respectively. The mortality rate was 1.9%, primarily due to hemorrhagic shock, septic shock, and multiple organ failure. Conclusion: Further studies are needed to investigate the long-term outcomes of interventions/surgeries in elderly patients to compare and evaluate the effectiveness of these methods.